(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2024)
The aim of the current research is to know the degree of inclusion of the twenty-first century skills included in the content of the social studies curriculum for the sixth grade in the basic education stage. To achieve this, a list of the twenty-first century skills included in the content of the social studies curriculum for the sixth grade was prepared based on the classifications of researchers in the field of twenty-first century skills. As the final list consisted of three skills and fifty-four indicators, the researcher used the descriptive approach (content analysis method), and the tool consisted of a content analysis card, which was designed based on the twenty-first century skills list to analyze the content of the social studies curriculum for the sixth grade. The results showed that the content of the social studies curriculum for the sixth grade included (3) twenty-first century skills out of (3) skills included in the list repeatedly (710) times. However, the inclusion of twenty-first century skills was at a low rate of (33.33%). Learning and innovation skills were the most frequent, and information technology and media skills were the least frequent. The results also showed a lack of progression and disparity in the rates of inclusion of some skills, as emphasis was placed on some more than others and were included in high percentages, compared to others, where there was no balance in the rates of their inclusion. Based on the above, the researcher proposed developing a specific strategy for the mechanism of including twenty-first century skills in the content of the social studies curriculum from one grade to another, taking into account the principle of gradualness in the rates of inclusion of these skills.